Becoming collaborative: a study of intra-organisational relational dynamics. Issue 1 (3rd April 2018) - Grove, Eloise; Dainty, Andrew; Thomson, Derek; Thorpe, Tony
Abstract : Purpose: The intra-organisational relationships of through-life support services providers are complex, especially given the multifaceted nature of the provision required. For example, capabilities within the UK highways maintenance arena must support engineering design, routine maintenance and the on-going management of the network. While collaboration in construction projects has formed a major research focus in recent years, there is a paucity of work examining collaboration in-flight. Design/methodology/approach: Through a micro-practices approach, two contracts delivering highway infrastructure maintenance and renewal services are examined to explore the intra-organisational relationships that determine the quality of service delivered. Findings: Despite the rhetoric of collaboration and integrated working that pervades the contemporary project discourse, there was a clear focus on addressing immediate technical and commercial concerns, rather than on creating the conditions for integrated working to flourish. On the occasions where the collaborative environment was prioritised, a more integrated service was delivered. Originality/value: In contrast to other accounts of the ways collaborative working shapes performance, this research reveals an acute need for a sustained collaborative effort; as soon as "collaborative working" was normalised, the level of integration and seamlessness of service was diminished. This questions normative notions of what defines collaborative working in projects and suggests a need for re-framing it as an on-going accomplishment of actors involved. Such a perspective resonates with notions of "organizational becoming", particularly in that attempts to foster collaboration are themselves constitutive of the unfolding and shifting nature of intra-organisational relationships that emerge in complex contractual arrangements.